Pengaruh Penggunaan E-Wallet Dan Gaya Hidup Terhadap Pola Belanja Mahasiswa STIE Mahardhika Surabaya - Nova Rahma Dhani; Laura Sitho Devi; Talabiah Susilowati; Nindya Kartika Kusmayati (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2025)
In today's digital era, the use of e-wallets is increasingly widespread and has begun to influence shopping habits, especially among students. Along with changes in lifestyle that are increasingly consumptive, shopping patterns have also shifted. This study raises two main factors, namely E-Wallet Use and Lifestyle, to see their influence on the shopping patterns of STIE Mahardhika Surabaya students. The approach used is quantitative with a survey method, where data was obtained through a questionnaire from 55 respondents and analyzed using multiple linear regression through SPSS. The results of the F test show a significance value of t table 2.007, while the lifestyle variable has a significance value of 0.003, with a calculated t of 3.109 which is greater than the t table 2.007. Therefore, it can be concluded that both have a significant partial influence on student shopping patterns